Internet and persons with disabilities: implication towards digital inclusion policy - Hashim, Junaidah; Wok, Saodah; Abdul Rahman, Rozailin; Haque, A. K. M. Ahasanul (2018)
OBJECTIVES OF THE STUDY  1. To determine the level of digital skills, usage and satisfaction of the Internet services among persons with disabilities;  To determine the relationships between digital skills and usage on satisfaction of the Internet services and persons with disabilities; and  To analyze the mediating effect of usage of the Internet on digital skills toward satisfaction services rendered to persons with disabilities.